Foreword - Board, Editorial (Ecological Questions, 2014)
Problems related to environmental conditions in towns and cities were partly dealt with in Issue 18 of "Ecological Questions". Issue 19 with 11 papers continues the aforementioned problems, though with much greater emphasis put on the concept of eco-cities.